Association Between Somatization and Nonmotor Symptoms Severity in People With Parkinson Disease. (January 2021) - Polo-Morales, Aranza; Alcocer-Salas, Ángel; Rodríguez-Violante, Mayela; Pinto-Solís, Daniella; Solís-Vivanco, Rodolfo; Cervantes-Arriaga, Amin
Objective: To assess the frequency of somatization and its association with motor, nonmotor symptoms, and quality of life in persons with Parkinson disease (PD). Methods: A cross-sectional case–control study was carried out. Assessments included the List of 90 Symptoms somatic factor (SCL-90-R SOM), Movement Disorder Society Unified Parkinson's Ratings Scale (MDS-UPDRS), Non-Motor Symptom Scale (NMSS), Montreal Cognitive Assessment (MoCA), and Parkinson Questionnaire-8 (PDQ-8). Results: A total 93 persons with PD and 93 controls were included. Somatization within the PD group was 2 times more frequent compared to the control group (43% vs 21.5%, P = .003). Persons with PD had higher NMSS total scores (48.6 ± 42.6 vs 28.3 ± 30.4, P = .001). Patients with PD with somatization had worst MDS-UPDRS, NMSS, MoCA, and PDQ-8 (all P < .05). Conclusion: Somatization is more frequent in persons with PD compared to healthy controls. Somatization in PD is associated with nonmotor symptoms and worst quality of life.